Self-reported sleep disturbance is significantly associated with depression, anxiety, self-efficacy, and stigma in Chinese patients with rheumatoid arthritis. Issue 4 (21st April 2023) - Liu, Ting; Geng, Yaqin; Han, Ziyin; Qin, Weiping; Zhou, Lanlan; Ding, Yu; Zhang, Zhengyu; Sun, Guomin
ABSTRACT: The objective of this article is to assess self-reported sleep disturbance and identify psychological, clinical, and sociodemographic factors that might influence sleep disturbance in patients with rheumatoid arthritis (RA). The study included 141 patients with confirmed RA (84.4% women, mean age 56.87 years). The Pittsburgh Sleep Quality Index, the Chinese version of rheumatoid arthritis self-efficacy scale, the Chinese version of Anxiety Depression Distress Inventory-27, the Chinese version of Stigma Scale for Chronic Illness, Visual Analogue Scale-Pain, disease activity index were used. Sleep disturbance was positively correlated with age, pain, disease activity, depression and anxiety, and stigma, while self-efficacy was correlated negatively with sleep disturbance. Multiple linear regression analysis revealed that depression, anxiety, self-efficacy, and stigma explained 77.4% of sleep quality variance. The data has demonstrated a suggestive relationship between low sleep quality and anxiety, depression, self-efficacy, and stigma. Patients reporting poor sleep, fatigue, and pain might have particular psychological intervention needs focusing on distress or anxiety symptoms, low self-efficacy, and high stigma.